INSTALLATION FOR STUDYING TRANSIENT CURRENTS IN DIELECTRIC LIQUIDS (World Science, 2022)
An experimental automated installation based on the Raspberry Pi3 Model B mini-computer and software for it is developed. By means of this installation, it is possible to carry out research of charging and discharging currents at different times in the range from 5·10-2 s to 4,5·103 s. Reversible currents up to voltages of 5 kV are studied using vacuum circuit breakers BB-5 (or BB-20, up to 20 kV). The installation allows detecting the accumulation of space charges both in the nearelectrode regions and in the volume of dielectric liquids. The installation allows to determine the mobility of charge carriers by the method of transient currents. The current flowing through the dielectric liquid is recorded by an electrometric amplifier, V7-30 or U5-11, which measures currents are in the range from 10-4 A to 10-12 A.The presented installation based on modern blocks and elements allows not only to carry out experimental studies with dielectric liquids of various types at the proper level, but also significantly improves the quality and efficiency of such studies.